A Safe and Efficient Strategy for the Rapid Elimination of Blood Lead In Vivo Based on a Capture–Fix–Separate Mechanism. Issue 31 (26th June 2019) - Wan, Mi Mi; Xu, Ting Ting; Chi, Bo; Wang, Meng; Huang, Yangyang; Wang, Qi; Li, Ting; Yan, Wen Qiang; Chen, Huan; Xu, Ping; Mao, Chun; Zhao, Bo; et al.
Abstract: Lead poisoning is an important problem because of its serious effects on human health. Yet a solution is not available due to an incomplete understanding of the state of lead ions in blood. Since most blood lead binds to hemoglobin (Hb) in red blood cells, identifying and capturing lead‐contaminated Hb in RBCs is important. Herein, a magnetic blood lead remover with hyperbranched poly(amidoamine)s (HPAM) as template/co‐adsorbent and core–shell mesoporous structure was synthesized. Lead‐containing Hb was selectively captured and then fixed by mesoporous channels. The magnetic separation technology was used to separate the magnetic remover from blood. A related blood lead clean‐up apparatus was used to remove lead from the blood of a pig in vivo. Results of physical/chemical characterizations, biocompatibility experiments, animal tests, and theoretical simulation verify the safety and efficiency of this removal strategy and the high efficiency of the blood lead clean‐up apparatus. Abstract : A treatment for lead poisoning, consisting of an Fe3 O4 nanoparticle coated with amine‐enriched hyperbranched poly(amidoamine)s, and an apparatus enabling the magnetic removal of nanoparticle‐associated, lead‐containing hemoglobin from the blood have been developed to treat lead poisoning in a safe and efficient way. This strategy enabled the removal of 75% of the lead from pig blood in vivo within 50 minutes.